Teach Effectively or Guide Wisely? Discussing the Application of Wisdom Approach to Language Teaching in Thai Higher Education - Chung, Ji Hye Jaime; Wei, Xiaoxia (International Journal of Language Education, 2020)
This study aimed to explore English language teachers’ perceptions and their classroom practices toward the application of teaching the ‘common good’ by incorporating a moral and ethical side of education to English Language Teaching (ELT). The data were collected by using a mixed-method approach consisting survey questionnaire, semi-structured interview, and class observations. Thirty teachers who taught English language at an international university located in Thailand participated in this study. The results revealed that the English language teachers do have a positive perception of the significance and value of cultivating students to achieve the common good in order to help them grow as virtuous citizens. However, their practices in classroom did not match the general perceptions as their behaviors were more focused towards linguistic effectiveness rather than wise guidance. It is recommended that language teachers raise awareness of the holistic aspect of education by valuing the social role of language in ELT.